Specification of models of entrepreneurship for stall owners and street vendors in the Plaza Mágica of Xilitla, area of huastecan exmigrants - Carreón Guillén, Javier; Hernández Valdés, Jorge (Trabajo Social UNAM, 2016)
The objective of the present paper is to specify the differences between stall owners and street vendors in a magic town in the face of public policies which support coffee growers, commerce and ecotourism. To this end a documentary study was carried out based on indexed data. Once the information was selected it was processed using matrix analysis of its content in order to specify the relationships between determining values of entrepreneurship. Based on the Theory of Relative Hardships, which holds that there are asymmetries between groups which are compared in similar contexts and establishes differences related to their government leader, the specified models point out two dimensions relative to innovation for the case of stall owners and conformity in the case of street vendors. With reference to the state of knowledge, the specifications of both models was discussed in order to anticipate scenarios of community development.